The relative effects of isolated and combined structures input and structured output on the acquisition of the English causative forms - Benati, Alessandro (2017)
The present study explores the effects of structured input and structured output when delivered in isolation or in combination on the acquisition of the English causative. Research investigating the effects of processing instruction and meaning output-based instruction has provided some interesting and sometimes conflicting results. Additionally, there are a number of issues (e. g., measuring a combination of structured input and structured output, measuring discourse-level effects) that have not been fully and clearly addressed. To provide answers to the questions formulated in this study, two classroom experiments were carried out. In the first study, fifty-four Chinese university students (age 18–20) participated. The participants were randomly assigned to four groups: structured input only group (n=13); structured output only group (n=15); combined structured input and structured output group (n=16); control group (n=10). In the second study, thirty school-age Greek learners (age 10–12) participated. The participants were randomly assigned to three groups: structured input only group (n=10); structured output only group (n=10); combined structured input and structured output group (n=10). Only subjects who participated in all phases of each experiment and scored lower than 60 % in the pre-tests were included in the final data collection. Instruction lasted for three hours. The control group received no instruction on the causative structure. Interpretation and production tasks were used in a pre-test and post-test design. The design included a delayed post-test battery (3 weeks after instruction) for both experiments. In the first study, the assessment tasks included an interpretation and production task at sentence-level, and an interpretation task at discourse-level. In the second study, an additional discourse-level production task was adopted along with the interpretation discourse-level task. The results indicated that learners who received structured input both in isolation and in combination benefitted more than learners receiving structured output only. These two groups were able to retain instructional gains three weeks later in all assessment measures.